Genetic susceptibility to fungal infection in children. Issue 6 (December 2020) - Ochoa, Sebastian; Constantine, Gregory M.; Lionakis, Michail S.
Abstract : Purpose of review: Fungal infections have steadily increased in incidence, emerging as a significant cause of morbidity and mortality in patients with iatrogenic immunosuppression. Simultaneously, we have witnessed a growing population of newly described inherited immune disorders that have enhanced our understanding of the human immune response against fungi. In the present review, we provide an overview and diagnostic roadmap to inherited disorders which confer susceptibility to superficial and invasive fungal infections. Recent findings: Inborn errors of fungal immunity encompass a heterogeneous group of disorders, some of which confer fungal infection-specific susceptibility, whereas others also feature broader infection vulnerability and/or noninfectious manifestations. Infections by Candida, Aspergillus, endemic dimorphic fungi, Pneumocystis, and dermatophytes along with their organ-specific presentations provide clinicians with important clues in the assessment of patients with suspected immune defects. Summary: The absence of iatrogenic risk factors should raise suspicion for inborn errors of immunity in children and young adults with recurrent or severe fungal diseases. Expeditious diagnosis and prompt initiation of antifungal therapy and management of complications are paramount to achieve remission of fungal disease in the setting of primary immunodeficiency disorders.